2014
DOI: 10.1007/s12031-014-0433-1
|View full text |Cite
|
Sign up to set email alerts
|

Bag5 Protects Neuronal Cells from Amyloid β-induced Cell Death

Abstract: The pathological mechanism of Alzheimer's disease (AD) needs to be elucidated. The Bcl-2 associated athanogene 5 (Bag5) is an important member in the Bag family. However, the role of Bag5 in AD has not yet been elucidated. In this study, we found that expression of Bag5 is elevated in the brains of AD transgenic Tg2576 mice at both mRNA levels and proteins. In vitro experiments indicated that Aβ1-42 treatment led to the upregulation of Bag5 in a dose-dependent manner. In addition, our results indicated that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…BAG5, as an important member of the BAG family, has been reported to demonstrate anti-apoptotic effects in prostate cancer (44). a previous study identified that BAG5 protected neuronal cells from amyloid β-induced cell death in Alzheimer's disease (45), and it has been demonstrated that BAG5 decreased the degradation of PTEN and maintained its stability through an ubiquitylation-dependent pathway (46). It has previously been observed that BAG5 may promote the accumulation of mutant p53 in tumors, and increase the gain-of-functions of mutant p53 (47).…”
Section: Discussionmentioning
confidence: 98%
“…BAG5, as an important member of the BAG family, has been reported to demonstrate anti-apoptotic effects in prostate cancer (44). a previous study identified that BAG5 protected neuronal cells from amyloid β-induced cell death in Alzheimer's disease (45), and it has been demonstrated that BAG5 decreased the degradation of PTEN and maintained its stability through an ubiquitylation-dependent pathway (46). It has previously been observed that BAG5 may promote the accumulation of mutant p53 in tumors, and increase the gain-of-functions of mutant p53 (47).…”
Section: Discussionmentioning
confidence: 98%
“…2A). As a member of the BAG protein family, which has been reported to enhance cell proliferation and survival (24), BAG5 is involved in several diseases via regulation of cell proliferation and gene expression (25)(26)(27)(28). Islet β-cell destruction and apoptosis serve an important role in the development of DM (29).…”
Section: Resultsmentioning
confidence: 99%
“…BAG5, a member of the BAG family, is considered a pathogenic gene involved in dopaminergic neuronal degeneration [ 16 , 20 , 40 , 41 ]. It was reported that physiological stress increases BAG5 expression [ 18 , 42 , 43 ]. However, our screen reveals the uniqueness of the BAG5 cochaperone in stress-mediated responses in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%